2009
DOI: 10.1080/00016340903117994
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of oral bovine lactoferrin compared to ferrous sulfate in pregnant women with iron deficiency anemia: A prospective controlled randomized study

Abstract: The results show that bovine lactoferrin has the same efficacy as ferrous sulfate in restoring iron deposits with significantly fewer gastrointestinal side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 14 publications
0
33
2
3
Order By: Relevance
“…Regarding potential Lf side effects, advanced clinical trials, including the treatment for H. pylori infection [42], iron deficiency anemia in pregnant women [43] and new-born sepsis [44] did not report any significant adverse effects or intolerance.…”
Section: Introductionmentioning
confidence: 98%
“…Regarding potential Lf side effects, advanced clinical trials, including the treatment for H. pylori infection [42], iron deficiency anemia in pregnant women [43] and new-born sepsis [44] did not report any significant adverse effects or intolerance.…”
Section: Introductionmentioning
confidence: 98%
“…In the present study we focused on lactoferrin (LF), an 80-kDa iron-binding glycoprotein of the transferrin family provided with anti-inflammatory and antimicrobial properties, which is able to decrease IL-6 in several experimental conditions [7]. LF is physiologically present in AF [8,9], and it is frequently administered to pregnant women for treating iron deficiency anemia [10]. …”
Section: Introductionmentioning
confidence: 99%
“…But till now in all well conducted trials no adverse effects have been reported. Furthermore, many children who received Bovine LF in the past, as a part of clinical trials, also reported no side effects [9,10]. However long term follow up of these enrolled neonates and children's needs to be viewed to answer this question.…”
Section: Discovery and Namingmentioning
confidence: 99%